Transforming Teacher Roles in Indonesia’s Digital Era: Enhancing Learning Effectiveness and Student Engagement - Ade Aspandi; Muhammad Azhar Muttaqin (MASI Mandiri Edukasi, 2025)
The rapid advancement of digital technology has significantly reshaped educational practices, requiring teachers to evolve from knowledge transmitters into dynamic facilitators of student-centred learning. This study adopts a library research method combined with content analysis to examine how teachers’ roles have transformed in response to technological innovation, particularly in enhancing learning effectiveness and student engagement. By reviewing a broad spectrum of recent scholarly articles, policy reports, and empirical studies, the research highlights that the integration of tools such as Learning Management Systems (LMS), Artificial Intelligence (AI), and interactive online platforms has fundamentally changed classroom dynamics and instructional design. For example, the use of gamified learning applications has been shown to increase student participation by fostering a sense of achievement, while adaptive learning software enables teachers to tailor content to individual progress, thereby improving comprehension and retention. As a result, educators are expected to develop advanced digital literacy, create innovative learning experiences, and adopt flexible strategies that respond to diverse learner needs. This shift requires sustained professional development, supportive institutional frameworks, and responsive educational policies that equip teachers to thrive in technology-rich environments. Moreover, meaningful integration of technology rather than its mere adoption has emerged as the key factor in driving improvements in motivation, engagement, and academic outcomes. This study contributes to the discourse on teacher professionalisation in the digital age and offers recommendations for policymakers and educational leaders to design effective training initiatives and support mechanisms for educators adapting to these evolving demands.